The Island of Alternatives: Power, Medical Science, and "Gentle Birthing" in Socialist Czechoslovakia - Hrešanová, Ema (Journal of the history of medicine and allied sciences, 2018)
Beginning in the early 1980s, medical experts and birthing women increasingly voiced criticism of what had long been the technocratic, depersonalized nature of obstetric treatment in Czechoslovakia, despite the limited opportunities for them to do so publicly. A few maternity hospitals responded to the complaints by introducing radically different regimens of care. This article examines the history of one reformist project that took place in the small town of Ostrov nad Ohří. Ostrov means "island" in Czech and, during the last decade of Communist rule in Czechoslovakia, the Ostrov hospital became an island of alternative obstetric care, embracing Leboyer's method of "gentle birthing," acupuncture, fathers in delivery rooms, and assorted technological innovations that aimed to spark fundamental change in familial and social relationships, and humanize childbirth. While many medical professionals decried these reforms as nonsensical and dangerous, a number of parents-to-be flocked to Ostrov to give birth, circumventing the official rules mandating that they receive healthcare in their area of residence. This proactive consumerist behavior among expectant parents, in tandem with the call of some physicians for more attention to individual and family needs, despite the opposing official political discourse, is evidence of a grassroots movement for market-oriented principles in healthcare that reflected broader societal change during the last decade of the Communist regime.
Keywords: porodnice; healthcare; birth chair; dospělí; Maternal-Child Nursing; Female; History, 20th Century; Adult; ženské pohlaví; state socialism; Hospitals, Maternity; Childbirth; lidé; porod; těhotenství; fathers at birth; ošetřovatelství v péči o matku a dítě; vedení porodu; Parturition; maternity care; dějiny 20. století; obstetric reform; Socialism; Leboyer; Delivery, Obstetric; socialismus; Velvet Revolution; perinatology; Pregnancy; Humans